SPECIFIC FEATURES OF DEVELOPING THE DIGITAL ECONOMY - Dilyora Khashimova Pakhritdinovna (Scholar Express Journals, 2025)
The article examines the main tasks in this area, based on the goals of digitization in service provision. Digitization in the service sector and the factors influencing it are identified. The implementation of priority projects for the digital transformation of regions is of great importance, and proposals and recommendations are put forward for the digitization of service sectors.
Keywords: digital economy; Digital Uzbekistan; Digital services